(untitled) (British Journal of Global Ecology and Sustainable Development, 2026)
This article examines state policy as a decisive factor in supporting the private sector and entrepreneurship in the modern economy. The central thesis is that entrepreneurship does not develop sustainably under spontaneous market conditions alone; it requires an institutional environment in which legal certainty, access to finance, skills formation, innovation support, and regulatory predictability are consistently maintained. International organizations treat small and medium-sized enterprises as a key source of employment, productive dynamism, and inclusive growth. At the same time, these enterprises face structural constraints that markets often do not eliminate on their own, especially in relation to credit access, digital transformation, innovation capacity, and resilience during economic shocks.